Morphological evaluation of bone surfaces after sectioning with diamond points or erbium: YAG laser (Pesquisa Odontológica Brasileira, 2000)
The purpose of this study was to analyze bone surfaces cut by Er:YAG laser or by diamond points. Five male rats (Rattus norvegicus albinus) were killed by lethal dose of phenobarbital, and selected bones were cut by Er:YAG laser at 300 mJ and 2 Hz, or by diamond points. The samples were submitted to evaluation through SEM at standard magnifications. By analyzing the surfaces, the authors could observe a pattern for each group, with a smoother surface in the laser cut group than in the diamond cut group. In higher magnifications, the images suggest melting and solidifying in the laser group. The authors conclude that the laser was effective in bone cutting. However, it was responsible for morphological changes that suggest a significant temperature increase.